PERAN BELANJA MODAL DALAM MEMODERASI PENGARUH MANAJEMEN LABA RIIL DAN MANAJEMEN LABA AKRUAL TERHADAP NILAI PERUSAHAAN - Riyanti, Yulia Eka; Murwaningsari, Etty (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study aims to obtain empirical evidence on the effect of real earnings management and accrual earnings management on firm value moderated by capital expenditures, as well as using control variables in the form of company size, female directors and financial flexibility. The research method used in this research is panel data regression analysis with the research sample, namely all energy and raw goods sector companies listed on the Indonesia Stock Exchange during 2019-2022. The results of the study show that real earnings management has a negative effect on firm value. Meanwhile, accrual earnings management and moderating role do not have a negative effect on firm value. In addition, only firm size as a control variable has an effect on firm value